2018
DOI: 10.1186/s12711-018-0422-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP profiling of worldwide goat populations reveals strong partitioning of diversity and highlights post-domestication migration routes

Abstract: BackgroundGoat populations that are characterized within the AdaptMap project cover a large part of the worldwide distribution of this species and provide the opportunity to assess their diversity at a global scale. We analysed genome-wide 50 K single nucleotide polymorphism (SNP) data from 144 populations to describe the global patterns of molecular variation, compare them to those observed in other livestock species, and identify the drivers that led to the current distribution of goats.ResultsA high degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
116
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 63 publications
(88 reference statements)
23
116
4
2
Order By: Relevance
“…This geographic structure is also supported by TreeMix and haplotype-based statistics ( figs. S11 and S12 ), in agreement with the scenario that the ancestors of present-day domestic goat populations followed distinct dispersal routes along the east-west axis of Afro-Eurasia ( 4 ) ( Fig. 2A, figs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This geographic structure is also supported by TreeMix and haplotype-based statistics ( figs. S11 and S12 ), in agreement with the scenario that the ancestors of present-day domestic goat populations followed distinct dispersal routes along the east-west axis of Afro-Eurasia ( 4 ) ( Fig. 2A, figs.…”
Section: Resultssupporting
confidence: 87%
“…Domestication presents an extreme shift of physiological and behavioral stress for free-living animals ( 1 ) to a high-density and disease-prone anthropogenic environment, especially for herbivores. The goat ( Capra hircus ) was one of the first domesticated livestock species, demonstrating remarkable adaptability and versatility ( 2, 3 ), and has been intimately associated with human dispersal ( 4 ). Recent studies have identified candidate targets of selection during goat domestication, including loci related to pigmentation, xenobiotic metabolism and milk production ( 5, 6 ); however, the evolutionary dynamics of key genes involved in adaptation during the early phase of domestication remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic plots of haplogroup frequencies show a considerable spatial differentiation, which resonates the strong phylogeography displayed by autosomal SNPs (Colli et al, 2018), but is in clear contrast with the phylogenetic structure displayed by mtDNA haplogroups (Luikart et al, 2001; Naderi et al, 2007, 2008; Zhao et al, 2014b, 2014a). Most likely, by a series of bottlenecks in the male lineage subcontinents have different major haplogroups, while none has a global-wide coverage: - Haplogroup Y2B is absent in Europe, Africa and west Asia, but became a major haplotype in east Asia and southeast Asian, where Y2A is not represented.…”
Section: Resultsmentioning
confidence: 79%
“…We differentiating the major Y-chromosomal haplogroups Y1AA, Y1AB, Y1B, Y2A and Y2B for 1720 domestic goats from 132 breeds by combining data from several sources as detailed per breed in Table 4: From the goat panel collected for the Econogene project, DNA samples of 353 male goats from 38 European or southwestern Asian breeds were analyzed by PCR amplification and dideoxy-sequencing of segments within the DBY, SRY and ZFY genes (Lenstra and Econogene Consortium, 2005) as described previously for bovine samples (Nijman et al, 2008; Edwards et al, 2011) and using the primers listed in Table 5. We used published data for 90 goats from 5 Portuguese breeds or from Morocco (Pereira et al, 2009), for 211 goats from 10 Asian breeds (Waki et al, 2015), for 181 goats from 8 Turkish breeds (Cinar Kul et al, 2015) and for 270 goats from 26 Spanish or Swiss breeds (Vidal et al, 2017). 362 DNA samples (57 breeds) from several sources, including the AdaptMap panel (Colli et al, 2018) were genotyped by the KASP assay (Table 4). For 90 goats from 15 breeds genotypes were obtained by B last searching of the ShortRead Archive (SRA). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation